Tenant - Sim, Mabel Jia Hui (2017)
In Singapore, the standard notion of family is recognised as the typical nuclear family with a Father, Mother, Child structure. However, the existence and unusual relationship dynamics amongst atypical families are not often known as less emphasis is given to these families in our social institutions. Belonging to an atypical family myself, my work seeks to study the relationship between my Father and I by charting its complex dynamics via a series of objects that offer a multiplicity of narratives, meanings and contradictions within a space structure that embodies the emotional and physical proximity between us.